2019
DOI: 10.4314/mmj.v31i3.6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of diabetic hand infections in Lagos, Nigeria

Abstract: Background Hand infections in diabetics can be a major cause of functional impairment .In patients with Tropical Diabetic hand syndrome prompt surgical intervention may salvage the hand, but return to premorbid function remain a challenge.Objectives A retrospective study of consecutive diabetic patients with hand infections was done in 2 tertiary institutions in Lagos,Nigeria to identify the epidemiology, modes of presentation, types of surgical intervention and outcomes oftreatment.Results Twenty one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Four needed either skin graft or groin flap. Mokifoya et al 19 in their study on 21 patients reported that two of their patients needed skin graft and two needed flap cover. They did a radial forearm artery flap, and both the cases suffered a partial loss.…”
Section: Discussionmentioning
confidence: 98%
“…Four needed either skin graft or groin flap. Mokifoya et al 19 in their study on 21 patients reported that two of their patients needed skin graft and two needed flap cover. They did a radial forearm artery flap, and both the cases suffered a partial loss.…”
Section: Discussionmentioning
confidence: 98%
“…TDHS is a rare but debilitating cause of morbidity, hospital admissions, and mortality amongst patients with diabetes, especially for patients in the tropics. 7,8 Compared with diabetic foot infection, TDHS seems to be less prevalent. [7][8][9] Some notable risk factors for TDHS include trauma, poor glycaemic control, and malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Compared with diabetic foot infection, TDHS seems to be less prevalent. [7][8][9] Some notable risk factors for TDHS include trauma, poor glycaemic control, and malnutrition. [7][8][9] Complications can range from sepsis, limb deformity, amputation, and death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate or late treatment can result in severe stiffness, contracture and ultimately loss of hand function. 13 Thus, early diagnosis and urgent aggressive treatment should be given to diabetic patients who present with hand infections to prevent long-term morbidity and death.…”
Section: Introductionmentioning
confidence: 99%